Parvovirus H1 selectively induces cytotoxic effects on human neuroblastoma cells - Lacroix, Jeannine; Leuchs, Barbara; Li, Junwei; Hristov, Georgi; Deubzer, Hedwig E.; Kulozik, Andreas; Rommelaere, Jean; Schlehofer, Jörg R.; Witt, Olaf (International journal of cancer, 2010)
Despite multimodal therapeutic concepts, advanced localized and high-risk neuroblastoma remains a therapeutic challenge with a long-term survival rate below 50%. Consequently, new modalities for the treatment of neuroblastoma, e.g., oncolytic virotherapy are urgently required. H-1PV is a rodent parvovirus devoid of relevant pathogenic effects in infected adult animals. In contrast, the virus has oncolytic properties and is particularly cytotoxic for transformed or tumor-derived cells of various species including cells of human origin. Here, a preclinical in vitro assessment of the application of oncolytic H-1PV for the treatment of neuroblastoma cells was performed. Infection efficiency, viral replication and lytic activity of H-1PV were analyzed in 11 neuroblastoma cell lines with different MYCN status. Oncoselectivity of the virus was confirmed by the infection of short term cultures of nonmalignant infant cells of different origin. In these nontransformed cells, no effect of H-1PV on viability or morphology of the cells was observed. In contrast, a lytic infection was induced in all neuroblastoma cell lines examined at MOIs between 0.001 and 10 pfu/cell. H-1PV actively replicated with virus titres increasing up to 5,000-fold within 48-96 hr after infection. The lytic effect of H-1PV was observed independent of MYCN oncogene amplification or differentiation status. Moreover, a significant G2-arrest and induction of apoptosis could be demonstrated. Infection efficiency, rapid virus replication and exhaustive lytic effects on neuroblastoma cells together with the low toxicity of H-1PV for nontransformed cells, render this parvovirus a promising candidate for oncolytic virotherapy of neuroblastoma.